Penentuan Siklus Estrus pada Kancil (Tragulus javanicus) Berdasarkan Perubahan Sitologi Vagina - -, Najamudin; -, Rusdin; -, Sriyanto; -, Amrozi; Agungpriyono, Srihadi; Laswardi Yusuf, Tuty (Jurnal Veteriner, 2010)
The aim of this study was to determine the estrus cycle and the length of estrus in Tragulus javanicuson the basis of its vaginal cytology. Vaginal swabs were collected daily at 7 am for two months. Smears ofthe swab were then prepared on glass slide and they were stained with Giemsa. Vaginal epithelial cells;parabasal, intermediet and superficial cells were counted and their percentages during proestrus, estrusand diestrus were determined. Diestrus was characterized by the absent of superficial cells in the vaginalepithel. Proestrus was characterized by the progressive increase in percentage of intermediet/superficialcells in vaginal epithel, whereas estrus was characterized by the presence of superficial/cornification cellsin most vaginal epithel. On the basis of its vaginal cytology, it was determined that the estrous period offemale Tragulus javanicus was 3 days (48-60 h) and the length was 11 days (10-14 day). The change in thecytology of vaginal epithelial cells appeared to a good marker to determine the estrus cycle phase of theTragulus javanicus
Keywords: Cytology, epithel, vagina, cycle estrous, parabasal, intermediet, superficisl snd cornification